Cytotoxicity Effect of Methanolic Extract of Buni’s Fruits (Antidesma bunius (L) Spreng) against Hela Cells - Endah Puspitasari (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Antidesma bunius (L) Spreng., also known as buni, has traditionally been used as hypoglycemic, anemia, siphilis and anticancer materials. Buni contains alkaloid, saponin, flavonoid and tannin. The fruit extract of buni was tested for its biological activity using BST (Brine Shrimp Lethality Test). Result showed toxic effect of methanolic extract of fruit. In the present study, the fruit was extracted with methanol and then used for cytotoxicity test based on direct counting method against HeLa cell line. By probit analysis, it is known that the IC50 of the methanolic crude extract is 3.117 μg/ml. The lack of its IC50 is caused by the cytotoxic compound that is less extracted and there are many other compounds are extracted by methanol